Dominant Modes of Tropospheric Ozone Variation over East Asia from GOME Observations - Yi Liu; Yuli Zhang; Yong Wang; Chuanxi Liu; Zhaonan Cai; Paul Konopka; Rolf Müller (Advances in Meteorology)
The variation in tropospheric ozone over East Asia was analyzed using tropospheric column ozone data measured by the Global Ozone Monitoring Experiment (GOME) satellite. An empirical orthogonal function (EOF) analysis was carried out to derive the dominant modes of the variation in the tropospheric ozone volume-mixing ratio (TOVMR). The EOF1 mode, which explained 61.5% of the total variance, showed a same-sign distribution over all of East Asia, with a belt of enhanced ozone concentrations around 40°N. The principal component of EOF1 (PC1) suggested that photochemical ozone production together with Brewer-Dobson circulation and subtropical westerly jet plays important roles in modulating the seasonal variation of the TOVMR; ozone-rich air produced by photochemical processes was transported from the stratosphere to the troposphere by BD circulation and this ozone-rich air was then blocked by the subtropical westerly jet and accumulated north of the jet. The EOF2 mode explained 29.2% of the total variance with an opposite-sign pattern on the north and south side of 35°N. When anticyclonic circulation transported ozone-poor air from the upwelling area over the Bay of Bengal towards the Tibetan Plateau during the onset of the Asian summer monsoon, tropospheric ozone in this region decreased dramatically.